Membedakan Takikardia Ventrikel dan Takikardia Supraventrikular Dengan Aberansi Pada Takikardia Dengan Kompleks QRS Lebar - Andi Haryanto; Yoga Yuniadi (The Indonesian Heart Association, 2013)
Wide complex tachycardia is a quite common rhythm found in ECG. Basicly there are 3 arrhytmia that can cause wide QRS complex tachycardia, which are: Ventricle tachycardia (VT) which is the most common (80%), Supraventricular tachycardia (SVT) with abberancy (15-20%), and Atrioventriculare Reentrant Tacycardia (AVRT) with antidromic conduction (1–6 %). Correct diagnosis in differentiating SVT with aberancy and VT is important, due to the different patophysiology and different mechanism they present. Thus the therapy and management will be different, and miss treatment proven to be fatal. Since ECG is still the main modality to provide the diagnosis in wide QRS complex tachycardia, many effort were done including the creation of algorhythms to help establish the diagnosis for wide complex tachycardia. The oldest and most widely used algorhythm is the Brugada algorhythm with respectable sensitivity and specificity. In 2007 Vereckei et al proposed a new algorhythm for differentiating VT and SVT with abberancy, and in 2008 Vereckei renew his previous algorhythm into only using single aVR lead to differentiate VT and SVT with abberancy, which was made solely based on the differences in the direction and velocity of the impulse. The latest method was again proposed by Brugada in 2010 which was called the ultrasimple Brugada criterion evethough there still haven’t many research that discuss the accuracy of such criteria.